Schools Transforming Character Education through Teacher Leadership: Exploration Study of Mobilizing Teachers in Indonesia’s Freedom Curriculum - Najmul Hadi; Bambang Saptono; Setiawan Edi Wibowo (Journal of Innovation and Research in Primary Education, 2026)
This exploratory qualitative study examines how teacher leadership mobilizes school communities to transform character education within Indonesia’s Freedom Curriculum (Kurikulum Merdeka). Conducted across five elementary schools in urban and rural settings of East Lombok, the study involved 10 Guru Penggerak teachers, alongside school leaders and parents as supporting informants. Data were collected over a six-month period (December 2024–April 2025) through semi-structured interviews, classroom and schoolwide observations, and document analysis, and were analyzed using inductive thematic analysis. The findings identify three observable domains of transformation: (1) the integration of character values into daily instructional practices through project-based and reflective learning activities, (2) the strengthening of school culture via teacher-led routines, visual character symbols, and collective norms, and (3) the expansion of character education beyond school through structured home–school collaboration. Across the participating schools, teachers reported consistent improvements in student participation, discipline, respect for peers, and responsibility, corroborated by observational data and parent feedback. The study demonstrates that character education reform becomes more coherent and sustainable when teacher leadership functions as a mobilizing force that aligns classroom practice, school culture, and community involvement. These findings contribute empirical evidence to policy discussions on scaling teacher-led character education within national curriculum reform.